Perceptions of Postgraduate Students Towards the use of Kahoot as A Formative Assessment Tool in an English Language Course (Raparin Journal of Humanities (RJH), 2022)
One of the transformations of the past decade has been the rapid and increased integration of the Internet and technological tools, particularly mobile-assisted learning (MAL) and gamification tool such as Kahoot, into EFL classrooms from across the world. Studies have shown that the gamified elements of such tools as Kahoot can enhance language learning performance and be utilised as influential teaching and assessment tools in language classrooms. Nevertheless, its application is yet quite new to EFL Kurdish classrooms; as observed, very few university instructors employ it. Furthermore, the acceptance of technological tools in general and Kahoot in particular by students and their perceptions towards its use is deemed significant due to its strong correlation with the overall language learning performance. Kahoot has been extensively researched in various educational contexts. Nevertheless, no study has reported students' perceptions of its use in EFL Kurdish classes. Therefore, the present study aimed at tackling Kurdish postgraduate students' perceptions towards implementing Kahoot in a six-week English language course and detecting their performance on Kahoot throughout the course, as well as showing gender differences in their perceptions. The study adopted a 24-item questionnaire on a 5-point Likert scale embedded in it two open-ended questions and students’ grades in the course. Almost all the students accepted the application and reported positive perceptions of using Kahoot in the course. However, Kahoot might lead to frustration and torpor on the students' part if not timed and designed correctly.